Hepatoprotective Triterpenoids and Saponins of Schefflera kwangsiensis - Wang, Yan; Zhang, Chun-Lei; Liu, Yan-Fei; Liang, Dong; Luo, Huan; Hao, Zhi-You; Chen, Ruo-Yun; Yu, De-Quan (Planta Medica, 2014)
Seven new triterpenoid saponins, schekwangsiensides A–G (1–7), and a new triterpenoid, schekwangsienin (8), together with nine known triterpenoids and saponins (9–17), were isolated from the aerial parts of Schefflera kwangsiensis. The structures of these compounds were elucidated on the basis of spectroscopic data analysis and chemical evidence. Furthermore, in in vitro assays, compounds 4, 8, 9, and 15 (10 µM) exhibited moderate hepatoprotective activities against D-galactosamine-induced HL-7702 cell damage.
Keywords: Araliaceae; Schefflera kwangsiensis; triterpenoid saponins; hepatoprotective; structure elucidation